AN ERROR ANALYSIS ON STUDENTS’ TRANSLATION - Julyanta Br Sitepu; Abdulloh Abdulloh; Sarsono Sarsono (STIBA IEC JAKARTA, 2021)
The research is conducted to find out what types of errors the students do most in translating English into Indonesian and Indonesian into English in order to improve the quality of the teaching for Private University Students. The description of the data is made by the writer based on the errors the students made in translation. The errors are articles, plural words, pronoun, noun phrases, gerund, participles, tenses, and word choices. The methodology used in this research is a qualitative research using the students’ translation from English into Indonesian and Indonesian into English. The research found the most error made by the students in translation is word choices 33.18 % or 154 errors in translating English into Indonesian and tenses 48.73% or 135 errors in translating Indonesian into English. The least error found in the students’ translation was gerund 0.64% or 3 errors in English into Indonesian and 0.72% or 2 errors Indonesian into English